Contribution of an extrinsic mechanism for the electrical polarization in BiMn2O5 ceramics - Fier, I. [UNESP]; Chinaglia, D. L. [UNESP]; Walmsley, L. [UNESP]; Pereira, E. C.; Rabelo, A. C.; Freitas, R. G. (American Institute of Physics (AIP), 2012)
DC conductivity, frequency dependent dielectric constant and pyroelectric coefficients, obtained from thermal stimulated depolarization current curves, in BiMn2O5 ceramics in the range of temperatures from 10 K to 320 K are reported. The data could be explained if it is assumed that a dipole defect is formed due to an oxygen vacancy and two manganese ions which have their valence changed to accept an electron. Copyright 2012 Author(s). This article is distributed under a Creative Commons Attribution 3.0 Unported License. [http://dx.doi.org/10.1063/1.4769752]